The contribution of wildfire to PM2.5 trends in the USA - Burke, Marshall; Childs, Marissa L.; de la Cuesta, Brandon; Qiu, Minghao; Li, Jessica; Gould, Carlos F.; Heft-Neal, Sam; Wara, Michael (Nature (London), 2023)
Steady improvements in ambient air quality in the USA over the past several decades, in part a result of public policy 1 , 2 , have led to public health benefits 1 – 4 . However, recent trends in ambient concentrations of particulate matter with diameters less than 2.5 μm (PM 2.5 ), a pollutant regulated under the Clean Air Act 1 , have stagnated or begun to reverse throughout much of the USA 5 . Here we use a combination of ground- and satellite-based air pollution data from 2000 to 2022 to quantify the contribution of wildfire smoke to these PM 2.5 trends. We find that since at least 2016, wildfire smoke has influenced trends in average annual PM 2.5 concentrations in nearly three-quarters of states in the contiguous USA, eroding about 25% of previous multi-decadal progress in reducing PM 2.5 concentrations on average in those states, equivalent to 4 years of air quality progress, and more than 50% in many western states. Smoke influence on trends in the number of days with extreme PM 2.5 concentrations is detectable by 2011, but the influence can be detected primarily in western and mid-western states. Wildfire-driven increases in ambient PM 2.5 concentrations are unregulated under current air pollution law 6 and, in the absence of further interventions, we show that the contribution of wildfire to regional and national air quality trends is likely to grow as the climate continues to warm. Ground- and satellite-based air pollution data from 2000 to 2022 quantify the contribution of wildfire smoke to stagnation or reversal in PM 2.5 concentration trends, showing that this contribution will grow as the climate continues to warm.